A high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate and preparation method thereof
By using ground polymer artificial aggregates in fiber-reinforced cement matrix and controlling the microhardness of the aggregate-matrix interface, the problem of insufficient mechanical properties of existing artificial aggregates is solved, and high-strength and high-strength fiber concrete is realized, promoting High-value application of artificial aggregates and optimization of performance of fiber-reinforced cement-based materials.
Patent Information
- Application Number
- CN202111416517.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-11-25
AI Technical Summary
The mechanical properties of existing polymer artificial aggregates cannot reach the strength level of natural aggregates, and there are safety hazards, making it difficult to achieve high-value applications.
By adding ground polymer artificial aggregate to the fiber-reinforced cement matrix, and adjusting the microhardness of the aggregate-matrix interface by incorporating granulated blast furnace slag powder, it promotes cracks to develop at the artificial aggregate, and achieves high-strength and high-strength fibers Concrete.
It realizes the high-value application of artificial aggregates and the performance optimization of fiber-reinforced cement-based materials, improves the compressive strength and ultimate tensile strain of concrete, and reduces safety hazards.
Smart Images

Figure CN116161906B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate and a preparation method thereof. Background Art
[0002] As an emerging technology in the field of solid waste recycling, the preparation of artificial aggregates is conducive to alleviating environmental problems caused by the accumulation of large amounts of industrial waste. At the same time, considering that natural aggregates are not inexhaustible, artificial aggregates can help alleviate the pressure on the exploitation of natural aggregate resources. At present, there are two major types of artificial aggregates on the market (calcined aggregates and cold-set aggregates), and the latter has greater market value and a wider range of applications. As a branch of cold-set aggregates, geopolymer artificial aggregates can be prepared by activating the silicon-aluminum phase industrial byproducts in an aqueous environment with alkali and crushing them. Although geopolymer artificial aggregates have low energy consumption, low carbon dioxide emissions and excellent heavy metal curing properties, their mechanical properties still cannot reach the strength level of natural aggregates formed by long-term geological action. Therefore, artificial aggregates are still "inferior substitutes" for natural aggregates, and concrete prepared from geopolymer artificial aggregates still has safety risks.
[0003] Engineered Cementitious Composites (ECC) is a new type of building material with high ductility, steady-state multi-crack cracking and strain hardening characteristics. With the continuous advancement of ECC design technology, how to fine-tune the mechanical properties of ECC so that it can gradually move towards higher ductility and higher strength is a frontier research field in ECC material design. In addition, the development of efficient recycling and treatment technology for solid waste has gradually become a major theme of the current era. Therefore, how to achieve high-performance utilization of waste in an economical and sustainable way is a major technical barrier to sustainable development in the current era. Summary of the invention
[0004] The technical feature of the present invention is to provide a high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate and a preparation method thereof, and the high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate, thereby realizing the high-value application of artificial aggregate and the performance optimization of fiber-reinforced cement-based materials.
[0005] The technical solution of the present invention is as follows:
[0006] A high-strength and high-tenacity fiber concrete based on geopolymer artificial aggregate, wherein the concrete comprises: a cement matrix, chopped fibers and geopolymer artificial aggregate;
[0007] The cement matrix is prepared by comprising the following components: cement, silica fume, water reducing agent and water;
[0008] The geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water, wherein the first cementitious material comprises fly ash and granulated blast furnace slag powder, wherein the fly ash accounts for 50%-80% of the mass of the first cementitious material, and the granulated blast furnace slag powder accounts for 20%-50% of the mass of the first cementitious material;
[0009] The microhardness of the geopolymer artificial aggregate is less than or equal to the microhardness at the interface of the cement matrix / geopolymer artificial aggregate, and the microhardness of the geopolymer artificial aggregate is less than the microhardness of the cement matrix.
[0010] Optionally, the first cementitious material further includes: industrial waste or domestic garbage.
[0011] Optionally, in the geopolymer artificial aggregate, the alkali activator accounts for 8%-16% of the mass of the first cementitious material, and the water accounts for 20%-45% of the mass of the first cementitious material.
[0012] Optionally, the concrete is prepared from the following components: cement, silica fume, water reducing agent and water, chopped fibers and geopolymer artificial aggregate.
[0013] Optionally, the chopped fibers include one or more of polyethylene fibers, polyvinyl alcohol fibers, polypropylene fibers and basalt fibers.
[0014] Optionally, the length of the chopped fibers is 6-18 mm, and the chopped fibers account for 1.5-2.0% of the volume of the concrete.
[0015] Optionally, the diameter of the geopolymer artificial aggregate is less than or equal to 4.75 mm.
[0016] Optionally, the compressive strength of the concrete is not less than 100 MPa, and the ultimate tensile strain of the concrete is not less than 1%.
[0017] A method for preparing high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate according to the present invention comprises the following steps:
[0018] A geopolymer artificial aggregate is provided, wherein the geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water, wherein the first cementitious material comprises fly ash and granulated blast furnace slag powder, wherein the fly ash accounts for 50%-80% of the mass of the first cementitious material, and the granulated blast furnace slag powder accounts for 20%-50% of the mass of the first cementitious material;
[0019] Pre-wetting the geopolymer artificial aggregate until it reaches a saturated surface dry state;
[0020] Mixing cement, silica fume and geopolymer artificial aggregate in a saturated surface dry state, and stirring to obtain a first mixture;
[0021] Adding water and a water reducing agent to the first mixture and stirring to obtain a slurry;
[0022] adding chopped fibers to the slurry and stirring to obtain a second mixture;
[0023] The second mixture is subjected to preliminary curing and water immersion curing in sequence to obtain the concrete.
[0024] Optionally, the method for preparing the geopolymer artificial aggregate comprises the steps of: mixing fly ash, granulated blast furnace slag powder and alkali activator in an aqueous solution environment to form a slurry; after the slurry is initially solidified, crushing it to a desired size using a crushing device, and then curing to obtain the geopolymer artificial aggregate.
[0025] Beneficial effects: The present invention utilizes the relatively low strength and fracture toughness of geopolymer artificial aggregate, adds it to a high-strength fiber cement matrix, changes the overall cracking toughness of the fiber cement matrix, and thus achieves fine regulation of the mechanical properties of the matrix; at the same time, because more than 20% of granulated blast furnace slag powder is added to the geopolymer artificial aggregate, it can regulate the microhardness of the interface between the geopolymer artificial aggregate and the cement matrix, ensuring that the microhardness of this aggregate-matrix interface is greater than the microhardness of the aggregate itself, avoiding cracks from developing along the aggregate-matrix interface, thereby inducing cracks to develop at the artificial aggregate, promoting the saturated multi-crack cracking phenomenon of artificial aggregate fiber concrete, and then achieving high strength and toughness based on weak aggregate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a curve of tensile stress and tensile strain of high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate in a specific embodiment of the present invention.
[0027] Figure 2 It is the microhardness distribution curve of aggregate, interface and matrix of high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0028] The present invention provides a high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate and a preparation method thereof. In order to more clearly and specifically describe the purpose, technical scheme and effect of the present invention, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] The embodiment of the present invention provides a high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate, wherein the concrete comprises: a cement matrix, chopped fibers and geopolymer artificial aggregate;
[0030] The cement matrix is prepared by comprising the following components: cement, silica fume, water reducing agent and water;
[0031] The geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water, wherein the first cementitious material comprises fly ash and granulated blast furnace slag powder, wherein the fly ash accounts for 50%-80% of the mass of the first cementitious material, and the granulated blast furnace slag powder accounts for 20%-50% of the mass of the first cementitious material;
[0032] The microhardness of the geopolymer artificial aggregate is less than or equal to the microhardness at the interface of the cement matrix / geopolymer artificial aggregate, and the microhardness of the geopolymer artificial aggregate is less than the microhardness of the cement matrix.
[0033] In this embodiment, the geopolymer artificial aggregate is added to a high-strength fiber-reinforced cement matrix by utilizing its relatively low strength and fracture toughness, thereby changing the overall cracking toughness of the fiber-reinforced cement matrix and achieving fine control of the mechanical properties of the matrix. At the same time, by adding more than 20% of granulated blast furnace slag powder into the preparation of the geopolymer artificial aggregate, the microhardness of the geopolymer artificial aggregate-cement matrix interface is regulated to ensure that the microhardness is greater than or equal to the microhardness of the geopolymer artificial aggregate itself, thereby avoiding cracks from developing along the aggregate-matrix interface, thereby inducing cracks to develop at the artificial aggregate, promoting the saturated multi-crack cracking phenomenon of the artificial aggregate fiber concrete, and then achieving high strength and toughness based on weak aggregate.
[0034] In this embodiment, the microscopic mechanical properties of the fiber concrete material are regulated by using geopolymer artificial aggregate, so as to prepare a high-strength and high-toughness fiber concrete material. In this embodiment, the high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate has a compressive strength of not less than 100 MPa and an ultimate tensile strain of not less than 1%.
[0035] Compared with the existing fiber concrete, the fiber concrete of this embodiment has the following technical advantages:
[0036] 1. The fiber concrete of this embodiment has the characteristics of high strength and high toughness.
[0037] 2. This embodiment uses geopolymer artificial aggregate, which can achieve micro-control of cement matrix and interface strength, thereby obtaining stronger and artificially controllable ductility and strain hardening properties.
[0038] 3. The existing natural aggregates are scarce, while this embodiment uses artificial aggregates based on waste materials, which can improve the green characteristics and sustainability of the material.
[0039] In one embodiment, the cement matrix is prepared from cement, silica fume, a water reducing agent and water.
[0040] In one embodiment, the chopped fibers include one or more of polyethylene (PE) fibers, polyvinyl alcohol (PVA) fibers, polypropylene (PP) fibers, and basalt fibers. Further, the chopped fibers are polypropylene fibers.
[0041] In one embodiment, the length of the chopped fibers is 6-18 mm, and the chopped fibers account for 1.5-2.0% of the volume of the concrete. The fiber length and fiber content can form sufficient fiber-matrix bridging force while meeting the fluidity requirements, thereby obtaining better strain hardening performance.
[0042] In one embodiment, the concrete is prepared from the following components: cement, silica fume, water reducing agent and water, chopped fibers and geopolymer artificial aggregate.
[0043] In this embodiment, the cement matrix is prepared by including the following components: cement, silica fume, water reducing agent and water. Further, the cement and silica fume are used as the second cementitious material, the cement accounts for 80%-100% of the mass of the second cementitious material, the silica fume accounts for 0%-20% of the mass of the second cementitious material, the water accounts for 16%-22% of the mass of the second cementitious material, and the water reducing agent accounts for 1.0%-1.5% of the mass of the second cementitious material.
[0044] In this embodiment, the geopolymer artificial aggregate is a saturated surface dry geopolymer artificial aggregate. Further, the saturated surface dry geopolymer artificial aggregate accounts for 20%-50% of the mass of the second cementitious material. According to the amount of different geopolymer artificial aggregates added, the fracture toughness of the fiber cement matrix can be adjusted. Within this range, the strain hardening performance required by the project can be effectively obtained.
[0045] In this embodiment, the geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water. In one embodiment, the alkali activator accounts for 8%-16% of the mass of the first cementitious material, and the water accounts for 20%-45% of the mass of the first cementitious material.
[0046] In one embodiment, the first cementitious material may also include: industrial waste or domestic garbage. By using the geopolymer artificial aggregate prepared from industrial waste, high-value utilization of industrial waste and performance optimization of fiber-reinforced cement-based materials are achieved.
[0047] That is, the geopolymer artificial aggregate is made of fly ash (as the main cementitious material) and granulated blast furnace slag powder (as the secondary cementitious material, the amount of which is not less than 20% of the total mass of the first cementitious material) as raw materials, and other industrial waste or domestic garbage (as supplementary cementitious materials) may or may not be added, and is obtained by being activated by an alkali activator and then crushed. Its microhardness is less than or equal to the microhardness at the interface of cement matrix / geopolymer artificial aggregate, and less than the microhardness of the cement matrix.
[0048] In one embodiment, the geopolymer artificial aggregate is crushed fine aggregate, and its diameter is less than or equal to 4.75 mm.
[0049] In one embodiment, the industrial waste is red mud.
[0050] In one embodiment, the domestic waste is municipal domestic waste incineration ash.
[0051] In one embodiment, the alkali activator is industrial grade sodium metasilicate or a mixture of sodium metasilicate and water glass.
[0052] In this embodiment, the strength of the geopolymer artificial aggregate is weaker than that of the cement matrix, but at the same time, it has a strong bonding property with the cement matrix, which prevents cracks from developing along the aggregate-matrix interface, thereby inducing cracks to develop at the artificial aggregate, promoting the saturated multi-crack cracking phenomenon of artificial aggregate fiber concrete, and thus achieving high strength and toughness.
[0053] In addition, this embodiment has the following advantages:
[0054] 1. This embodiment prepares geopolymer artificial aggregate based on silicon-aluminum phase industrial byproducts and waste, which is green and environmentally friendly and can help solve the problem of industrial byproducts and waste accumulation.
[0055] 2. This embodiment utilizes the low strength characteristics of geopolymer artificial aggregate to regulate the performance of the fiber-reinforced cement matrix, thereby promoting its saturated multi-crack cracking, achieving high-value utilization of industrial by-products / waste materials and optimizing the performance of fiber-reinforced cement-based materials.
[0056] 3. This embodiment provides a new application method of geopolymer artificial aggregate, which provides new possibilities for replacing natural aggregates and solves the problem of aggregate shortage to a certain extent.
[0057] The embodiment of the present invention provides a method for preparing high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate, which comprises the following steps:
[0058] S10, providing a geopolymer artificial aggregate, wherein the geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water, wherein the first cementitious material comprises fly ash and granulated blast furnace slag powder, wherein the fly ash accounts for 50%-80% of the mass of the first cementitious material, and the granulated blast furnace slag powder accounts for 20%-50% of the mass of the first cementitious material;
[0059] S20, pre-wetting the geopolymer artificial aggregate until it reaches a saturated surface dry state;
[0060] S30, mixing cement, silica fume and geopolymer artificial aggregate in a saturated surface dry state, and stirring (5-10 minutes) to obtain a first mixture;
[0061] S40, adding water and a water reducing agent to the first mixture, and stirring (about 15 minutes) to obtain a uniform slurry;
[0062] S50, adding chopped fibers to the slurry and stirring (for about 5 minutes) to obtain a second mixture;
[0063] S60, performing preliminary curing and water immersion curing on the second mixture in sequence to obtain concrete.
[0064] In step S10, in one embodiment, the method for preparing the geopolymer artificial aggregate includes the steps of: mixing fly ash, granulated blast furnace slag powder and alkali activator in an aqueous solution environment to form a slurry; after the slurry is initially solidified, crushing it to a desired size using a crushing device, and then curing it to obtain the geopolymer artificial aggregate.
[0065] In one embodiment, the geopolymer artificial aggregate is cured at room temperature for more than 28 days after being crushed.
[0066] In step S60, the purpose of the preliminary curing is to obtain hardened concrete for easy demoulding; the purpose of the immersion curing is to allow the concrete to fully complete the early hydration process.
[0067] Furthermore, after the step of water curing, the steps of steam curing and temperature curing are sequentially performed to obtain concrete with stable performance. The purpose of further steam curing and temperature curing is to enable the concrete to obtain higher mechanical properties and improve the stability of the mechanical properties of the concrete.
[0068] In one embodiment, the initial curing temperature ranges from 21 to 25° C., and the curing time is 24 to 48 hours.
[0069] In one embodiment, the immersion curing time is 27 days.
[0070] In one embodiment, the steam curing humidity is 95%-100%, the curing temperature range is 60° C.-90° C., and the curing time is 5 days.
[0071] In one embodiment, the temperature range of the temperature curing is 60°C-90°C, and the temperature curing time is 7 days.
[0072] The present invention will be further described below by means of specific examples.
[0073] Example:
[0074] In this specific embodiment, the raw materials and preparation method of geopolymer artificial aggregate are as follows:
[0075] (1) Raw materials: The geopolymer artificial aggregate uses fly ash as the main cementitious material, accounting for 80% of the mass of the first cementitious material, and granulated blast furnace slag powder as the secondary cementitious material, accounting for 20% of the mass of the first cementitious material; the alkali activator uses industrial grade sodium metasilicate, the modulus (the molar ratio of silicon dioxide to sodium oxide in the alkali activator) is 0.94, and the mass ratio of the alkali activator to the first cementitious material is 12%; the mass ratio of water to the first cementitious material is 35%.
[0076] (2) Preparation method: First, fly ash, granulated blast furnace slag powder and industrial sodium metasilicate are stirred evenly, and then water is added to obtain slurry; the slurry is poured into a mold, cured at room temperature for 24 hours, taken out after hardening, and crushed to less than 4.75 mm with a crusher, and cured at room temperature for 28 days. The water absorption rate and apparent density of the obtained geopolymer artificial aggregate are 24.6% and 2050 kg / m respectively. 3 .
[0077] In this specific embodiment, the raw materials and preparation method of the high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate are as follows:
[0078] (1) Pre-wetting the prepared geopolymer artificial aggregate to achieve saturated surface dryness.
[0079] (2) Raw materials: Cement and silica fume are used as the second cementitious material, and their weight accounts for 80% and 20% of the second cementitious material respectively; the weight of saturated surface dry geopolymer artificial aggregate accounts for 48% of the second cementitious material; the weight of added water accounts for 17.1% of the second cementitious material; the weight of added water reducer (solid) accounts for 1.32% of the second cementitious material. The chopped fiber is polyethylene (PE) fiber, and its volume accounts for 2% of the total volume of concrete.
[0080] (3) Preparation method: First, pre-wet the geopolymer artificial aggregate to achieve saturated surface dryness; mix cement, silica fume and saturated surface dry geopolymer artificial aggregate and stir for 8 minutes; add water and water reducer and stir for 15 minutes to obtain a uniform slurry; add chopped fibers and stir for 5 minutes; pour the stirred slurry into a compression and tensile mold, cure at room temperature for 24 hours, take it out after hardening, and then test it on the 28th day after curing.
[0081] In this specific embodiment, the test performance of high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate is as follows:
[0082] Compressive strength: 121MPa.
[0083] Tensile strength: 10.1MPa.
[0084] Ultimate tensile strain: 9.9%.
[0085] Average crack width at limit state: 60μm.
[0086] In this specific embodiment, the tensile stress-strain curve of the high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate is as follows: Figure 1 shown.
[0087] In this specific embodiment, the microhardness distribution curves of the aggregate, interface and matrix of the high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate are as follows: Figure 2 As shown in the figure, the microhardness of the geopolymer artificial aggregate in the specific embodiment is less than or equal to the microhardness at the interface of the cement matrix / geopolymer artificial aggregate, and is less than the microhardness of the cement matrix.
Claims
1. A high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate, characterized in that: The concrete comprises: a cement matrix, chopped fibers and geopolymer artificial aggregate; The cement matrix is prepared by comprising the following components: cement, silica fume, water reducing agent and water; The geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water, wherein the first cementitious material comprises fly ash and granulated blast furnace slag powder, wherein the fly ash accounts for 50%-80% of the mass of the first cementitious material, and the granulated blast furnace slag powder accounts for 20%-50% of the mass of the first cementitious material; The microhardness of the geopolymer artificial aggregate is less than or equal to the microhardness at the cement matrix / geopolymer artificial aggregate interface, and the microhardness of the geopolymer artificial aggregate is less than the microhardness of the cement matrix; In the geopolymer artificial aggregate, the alkali activator accounts for 8%-16% of the mass of the first cementitious material, and the water accounts for 20%-45% of the mass of the first cementitious material; The length of the chopped fibers is 6-18 mm, and the chopped fibers account for 1.5-2.0% of the volume of the concrete; The diameter of the geopolymer artificial aggregate is less than or equal to 4.75 mm; In the cement matrix, the cement and silica fume are used as the second cementitious material, the cement accounts for 80%-100% of the mass of the second cementitious material, the silica fume accounts for 0%-20% of the mass of the second cementitious material, the water accounts for 16%-22% of the mass of the second cementitious material, and the water reducer accounts for 1.0%-1.5% of the mass of the second cementitious material; The geopolymer artificial aggregate is a saturated surface-dry geopolymer artificial aggregate, and the saturated surface-dry geopolymer artificial aggregate accounts for 20%-50% of the mass of the second cementitious material; The preparation method of the geopolymer artificial aggregate comprises the following steps: mixing fly ash, granulated blast furnace slag powder and alkali activator in an aqueous solution environment to form a slurry; after the slurry is initially solidified, crushing it to a desired size using a crushing device, and then curing it to obtain the geopolymer artificial aggregate.
2. The high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate according to claim 1, characterized in that: The first gelling material also includes: industrial waste or domestic garbage.
3. The high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate according to claim 1, characterized in that: The concrete is prepared from the following components: cement, silica fume, water reducing agent and water, short-cut fibers and geopolymer artificial aggregate.
4. The high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate according to claim 1, characterized in that: The chopped fibers include one or more of polyethylene fibers, polyvinyl alcohol fibers, polypropylene fibers and basalt fibers.
5. The high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate according to claim 1, characterized in that: The compressive strength of the concrete is not less than 100 MPa, and the ultimate tensile strain of the concrete is not less than 1%.
6. A method for preparing high-strength and high-toughness fiber concrete based on geopolymer artificial aggregate according to any one of claims 1 to 5, characterized in that: Includes steps: A geopolymer artificial aggregate is provided, wherein the geopolymer artificial aggregate is prepared by comprising the following components: a first cementitious material, an alkali activator and water, wherein the first cementitious material comprises fly ash and granulated blast furnace slag powder, wherein the fly ash accounts for 50%-80% of the mass of the first cementitious material, and the granulated blast furnace slag powder accounts for 20%-50% of the mass of the first cementitious material; Pre-wetting the geopolymer artificial aggregate until it reaches a saturated surface dry state; Mixing cement, silica fume and geopolymer artificial aggregate in a saturated surface dry state, and stirring to obtain a first mixture; Adding water and a water reducing agent to the first mixture and stirring to obtain a slurry; adding chopped fibers to the slurry and stirring to obtain a second mixture; The second mixture is subjected to preliminary curing and water immersion curing in sequence to obtain the concrete; The preparation method of the geopolymer artificial aggregate comprises the following steps: mixing fly ash, granulated blast furnace slag powder and alkali activator in an aqueous solution environment to form a slurry; after the slurry is initially solidified, crushing it to a desired size using a crushing device, and then curing it to obtain the geopolymer artificial aggregate.
Citation Information
Patent Citations
High-strength high-toughness cement-based composite material with saturated multiple cracking using coarse river sand as fine aggregate
CN110282932A
Geopolymer artificial aggregate based on crushing method and preparation method thereof
CN112479615A